2019
DOI: 10.1007/s00265-019-2722-8
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionary perspective on the development of primate sociality

Abstract: It is now well established that sociality plays a crucial role in primates. For example, among non-human primates, individuals with strong social bonds significantly increase their fecundity, reproductive success, offspring survival and longevity. Also in humans, social integration positively affects psychological stress, health and survival. However, despite the evidence that sociality is a fundamental fitness trait, relatively little is known about how sociality develops. Previous studies are mainly limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Sociality is the tendency to involve oneself with others spontaneously ( De Jaegher et al, 2010 ; Amici and Widdig, 2019 ; Ichikawa et al, 2021 ); humans who interact based on sociality change their environments ( Sebanz et al, 2006 ). Social interactions are observed in living organisms including non-humans and serve as a foundation for various activities.…”
Section: Introductionmentioning
confidence: 99%
“…Sociality is the tendency to involve oneself with others spontaneously ( De Jaegher et al, 2010 ; Amici and Widdig, 2019 ; Ichikawa et al, 2021 ); humans who interact based on sociality change their environments ( Sebanz et al, 2006 ). Social interactions are observed in living organisms including non-humans and serve as a foundation for various activities.…”
Section: Introductionmentioning
confidence: 99%
“…While these studies effectively recapitulated many elements of the rodent literature, they require navigating a number of practical challenges such as the prolonged developmental timelines where sexual maturity is not reached until 3-4 years of age, where young adulthood is not reached until after 5 years of age, and where housing requirements present limitations regarding the assessment of social behaviors (15,17). Further, a comprehensive review of the literature by Amici et al (18) suggested that most developmental changes in macaque sociality occur between 2 and 3 years, making logistics and cost of colony management for experiments particularly challenging. In order to overcome this challenge, we aimed to develop and characterize a translationally relevant and practical non-human primate model of maternal immune activation using marmosets.…”
Section: Introductionmentioning
confidence: 99%
“…It seems undoubted that to be social comes first, starting from the long background of ape social worlds. The common background of deep sociality in the great apes suggests from the genetic and fossil evidence that this phenomenon goes back some 20 million years (Amici & Widdig, 2019; Dunbar & Shultz, 2007; Shultz & Dunbar, 2014; Simons, 2002). It cannot therefore explain everything new in Homo , except through changes in the nature and levels of sociality.…”
Section: Introductionmentioning
confidence: 99%